Breeding and conservation ecology of Asian hornbills (AVES: Bucerotidae) in Kinabatangan, Sabah / Ravinder Kaur Kirpal Singh - Ravinder Kaur , Kirpal Singh (2020)
Eight species of Asian hornbills persist in the Kinabatangan, Sabah. These are the critically endangered Helmeted hornbill (Rhinoplax vigil), endangered Wrinkled hornbill (Rhabdotorrhinus corrugatus) and White-crowned hornbill (Berenicornis comatus), three vulnerable species Rhinoceros hornbill (Buceros rhinoceros), Black hornbill (Anthracoceros malayanus) and Wreathed hornbill (Rhyticeros undulatus), the near threatened Bushy-crested hornbill (Anorrhinus galeritus) and the least concern Oriental Pied hornbill (Anthracoceros albirostris convexus). Hornbills are mainly frugivorous and they are known as secondary cavity-nesting birds. In Kinabatangan, the hornbill populations have been declining over the past few decades. Past timber extraction has left behind highly degraded forest patches in the Kinabatangan and this may constrain the availability of tree cavities and food plants for hornbills. To investigate the availability of these resources, 30 plots (250m x 250m) in a 10km2 forest were systematically established and surveyed. Imperfect detection along transect due to concealed tree cavities was addressed in the zero-inflated Poisson process occupancy model. Fourteen trees with cavities were detected in 10 out of 30 plots (ψ =0.33). However, the Bayesian prior distribution with the data collected revealed that trees with cavities occupied 25 plots out of 30 plots (ψ =0.82). Nineteen empty tree cavities were detected, formed mainly in genus Madhuca (family Sapotaceae). Thirty-two fig trees, believed to be the main food resource of hornbills, were detected in 20 out of 30 plots (ψ =0.66). Based on the Bayesian prior distribution and the data collected, fig trees occupied 27 plots out of 30 plots (ψ =0.87). For both trees with cavities and fig trees, the model yielded a higher estimate of occupancy as it factors in detectability. Due to financial and manpower constraints, the occurrence of hornbills was investigated in place of abundance estimates. Five species (i.e. Rhinoceros hornbill, Wrinkled hornbill, Black hornbill, Bushy crested hornbill and Oriental Pied hornbill) were common, perhaps due to their affinity towards lowland forests and diet diversity. Opportunistic observations also yielded additional information on hornbill diet and behaviours. The mean internal temperatures and humidity levels of six natural nests were explored and it ranged from 25.8-28.8°C and 88.2-99.8% respectively, suggesting the importance of low temperature and high humidity conditions within the cavity. These parameters may influence the success of incubation and egg hatching. Therefore, achieving these parameters was imperative in the development of artificial nest boxes in this study. Subsequently, these boxes attracted several hornbill species. In addition, six abandoned natural nest cavities of Oriental Pied hornbills were restored, resulting in the fledging of nine chicks. The restored cavities were used swiftly, another indication of the lack of suitable natural cavities. The poorly studied Helmeted hornbill was observed from 2013 to 2018. They nested in the dry months, inside a Shorea pauciflora tree. Their breeding diet consisted of figs and stick insects. Helmeted hornbills invest greatly in parental care, with the female staying inside the cavity for five months with the chick while the male supplied food. In conclusion, this study describes the population state of hornbills in Kinabatangan, provides new information on Helmeted hornbill parental care, diet preferences and breeding duration, general hornbill plant based diet and improvements in artificial nest box designs. Furthermore, wildlife managers are provided with insights into the availability of hornbill key resources for their management plans.